Informed Consent in Clinical Trials with Reference to Information Disclosure to Patient-Subjects. - Yuhanif Yusof; Anisah Che Ngah; Zaki Morad Mohamad Zaher (Universiti Kebangsaan Malaysia, 2014)
The aim of this study was to examine the aspect of information disclosure by doctor-investigator during the process of obtaining informed consent in clinical trials.